Risk factors nonpsychotic mental and behavioral disorders in a social stress - Nikoriak Руслана (Psychosomatic Medicine and General Practice, 2019)
Introduction. In recent years, there has been increased attention of researchers to the problems of psychogenic diseases due to the increasing prevalence of this pathology and a deeper understanding of their role in shaping social maladaptation. The social crisis, the ongoing, almost 4 years of hostilities in the east of Ukraine, the forced labor migration of the population in search of financial support for the family, and sometimes the only opportunity to survive in the conditions of socio-economic crisis have led to the disadaptation of a large part of society. Purpose. Investigate risk factors for non-psychotic mental and behavioral disorders among migrant workers and combatants in order to prevent mental illness. Materials and methods. Clinical-psychopathological and experimental-psychological studies of labor migrants and demobilized combatants were conducted in 2 districts of the Chernivtsi region, namely, Storozhinets and Zastavna districts. Results. The screening test surveyed 150 people - 80 combatants and 70 migrant workers. Stressful were: 30 combatants and 40 migrant workers. Risk factors such as low socioeconomic status, the absence of a large proportion of migrant workers and demobilized material-labor combatants at the time of the survey, lack of "full" understanding in the family and support from them led to emotional experiences. The "unfairness" and "frequent" undervaluation of undervalued labor by migrant workers provoked the onset of anxiety and craving for drinking. Demobilized combatants were "indifferent" to their problems on the part of society caused irritability, aggression, which were exacerbated by the use of psychoactive substances. Thus, the set of stressors (migrational, combat, psychological) has led to significant changes in the lives of forced labor migrants and demobilized combatants in Eastern Ukraine, provoked social disadaptation in society and impaired the quality of life and social functioning in society. These significant stressors have created a threatening background to the mental health disorder of Ukrainians. Therefore, labor migration and participation in combat are extremely strong stressors that deplete the individual both physically and mentally and in need of effective state and medical assistance.